BARRIER TO INNOVATION IN DEVELOPING COUNTRIES’ FIRMS: EVIDENCE FROM NIGERIAN SMALL AND MEDIUM SCALE ENTERPRISES - Nassar, Moshood Larenwaju; Faloye, Dotun Olaleye (European Scientific Journal, ESJ, 2015)
This paper explored the barriers to innovation in the Nigerian Small and Medium scale Enterprises (SMEs). The data used in this research were derived from the study of 996 SMEs that were selected in southwestern Nigeria using stratified random sampling technique. The data were collected using questionnaire and face-to-face interviews with 38 SME Owners/Managers in the study area. The data collected were analyzed using appropriate descriptive statistics. The study identified the major barriers to innovation in the Nigerian SMEs to include inadequate financial means and venture capital companies to sponsor new innovation, inadequate government assistance, poor infrastructural facilities, small size of company and market, lack of motivation for new innovation, inadequate research and development facilities within the firm, and lack of opportunities for cooperation with other firms and research institutions. The paper concluded that the barriers to innovation in the Nigerian SMEs need to be reduced or eliminated inorder to enhance their innovative performance and be at par with the rest of the SMEs from across the world now that the market place is open to all players.